Potential gene exchange between Bacillus thuringiensis subsp. kurstaki and Bacillus spp. in soil in situ - Donnarumma, Francesca; Paffetti, Donatella; Stotzky, Guenther; Giannini, Raffaello; Vettori, Cristina (Soil Biology and Biochemistry, 2010)
The possible transfer of genes from Bacillus thuringiensis subsp. kurstaki (Btk) to indigenous Bacillus spp. was investigated in soil samples from stands of cork oak in Orotelli (Sardinia, Italy) collected 5 years after spraying of the stands with a commercial insecticidal preparation (FORAY 48B) of Btk. Two colonies with a morphology different from that of Btk were isolated and identiﬁed as Bacillus mycoides by morphological and physiological characteristics and by 16S rDNA analysis. Ampliﬁcation by the polymerase chain reaction (PCR) of the DNA of the two isolated B. mycoides colonies with primers used for the identiﬁ- cation of the Btk cry genes showed the presence of a fragment of 238 bp of the cry1Ab9 gene that had a similarity of 100% with the sequence of the cry1Ab9 gene present in GenBank, indicating that the isolates of B. mycoides acquired part of the sequence of this gene from Btk. No cells of Btk or B. mycoides carrying the 238-bp fragment of the cry1Ab9 gene were isolated from samples of unsprayed control soil. However, the isolates of B. mycoides were not able to express the partial Cry1Ab protein. Hybridization with probes for IS231 and the cry1Ab9 gene suggested that the inverted repeated sequence, IS231, was probably involved in the transfer of the 238-bp fragment from Btk to B. mycoides. These results indicate that transfer of genes between introduced Btk and indigenous Bacillus spp. can occur in soil under ﬁeld conditions.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Bacillus mycoides; Bacillus spp; bacillus thuringiensis subsp; Bacillus thuringiensis subsp. kurstaki; cry genes; Horizontal gene transfer; kurstaki; Natural soil environment